Single‐cell RNA‐seq reveals interferon‐induced guanylate‐binding proteins are linked with sarcopenia. Issue 6 (26th September 2022) - Peng, Zhi; Zhang, Ruoyu; Kuang, Xiaolin; Yu, Chen; Niu, Shiwei; Du, Yongjun; Lu, Di; Li, Shaobo; Teng, Zhaowei; Lu, Sheng
Abstract: Background: Sarcopenia is defined as an age‐related progressive loss of muscle mass and/or strength. Although different factors can contribute to this disease, the underlying mechanisms remain unclear. We assessed transcriptional heterogeneity in skeletal muscles from sarcopenic and control mice at single‐cell resolution. Methods: A mouse model was established to study sarcopenic skeletal muscles. Single‐cell RNA‐seq was performed on tibialis anterior (TA) muscle cells collected from sarcopenic and control mice. A series of bioinformatic analyses were carried out to identify and compare different cell types under different conditions. Immunofluorescence staining and western blotting were used to validate the findings from single‐cell experiments. Tube formation assays were conducted to further evaluate the effects of Gbp2 on endothelial cells during angiogenesis. Results: A murine sarcopenia model was successfully established using a senescence‐accelerated mouse strain (SAMP6, n = 5). Sarcopenia phenotype was induced by administration of dexamethasone (20 mg/kg) and reduced physical activity. Senescence‐resistant mice strain (SAMR1) and SAMP6 strain with similar activity but injected with PBS were recruited as two control groups. As signs of sarcopenia, body weight, muscle cell counts and cross‐sectional fibre area were all significantly decreased in sarcopenic mice ( P value = 0.004, 0.03 and 0.035, respectively). After quality control, 13 612 TA muscle single‐cell transcriptomes were retained for analysis. Fourteen cell clusters were identified from the profiled cells. Among them, two distinct endothelial subtypes were found to be dominant in the sarcopenia group (42.2% cells) and in the two control groups (59.1% and 47.9% cells), respectively. 191 differentially expressed genes were detected between the two endothelial subtypes. Sarcopenia‐specific endothelial cell subtype exhibited a dramatic increase in the interferon family genes and the interferon‐inducible guanylate‐binding protein (GBP) family gene expressions. For example, Igtp and Gbp2 in sarcopenic endothelial cells were 5.4 and 13.3 times higher than those in the control groups, respectively. We further validated our findings in muscle specimens of sarcopenia patients and observed that GBP2 levels were increased in endothelial cells of a subset of patients (11 of 40 patients, 27.5%), and we identified significantly higher CD31 and GBP2 co‐localization ( P value = 0.001128 ). Finally, we overexpressed Gbp2 in human umbilical vein endothelial cells in vitro . The endothelial cells with elevated Gbp2 expression displayed compromised tube formation. Conclusions: Our single‐cell‐based results suggested that endothelial cells may play critical roles in sarcopenia development through interferon‐GBP signalling pathways, highlighting new therapeutic directions to slow down or even reverse age‐related sarcopenia.